Methylprednisolone improves the quality of liquid preserved boar spermatozoa in vitro and reduces polymorphonuclear neutrophil chemotaxis and phagocytosis - Li, Yanbing; Wang, Hechuan; Wang, Shuo; Zhang, Qun; Zhang, Han; Li, Tianfeng; Wang, Qian; Guo, Minghui; Feng, Heze; Song, Yulun; Wei, Guosheng; Li, Jingchun (Frontiers in Veterinary Science, 2023)
After artificial insemination, immune cells such as polymorphonuclear neutrophils will be recruited into the genital tract and induce endometrial inflammation, adversely affecting the spermatozoa. This study aimed to analyze the effect of methylprednisolone on boar spermatozoa quality of in vitro liquid preservation and chemotaxis and phagocytosis of polymorphonuclear neutrophils toward boar spermatozoa. Various concentrations of methylprednisolone were added to the extender and analyzed for their effects on spermatozoa motility, kinetic parameters, malformation rate, T-AOC levels, H2O2 content, mitochondrial membrane potential and acrosome integrity. Testing of methylprednisolone on chemotaxis and phagocytosis of polymorphonuclear neutrophils toward spermatozoa induced by LPS. The results showed that an extender containing 2×10-7 mmol/L methylprednisolone was the most effective for preserving boar spermatozoa during in vitro liquid preservation at 17°C. It effectively improved spermatozoa motility, kinetic parameters, T-AOC levels, mitochondrial membrane potential and acrosome integrity, reducing the malformation rate and H2O2 content. Meanwhile, the chemotaxis and phagocytosis of polymorphonuclear neutrophils toward spermatozoa under LPS induction were inhibited in a concentration-dependent manner. In conclusion, methylprednisolone has positive implications for improving in vitro liquid preserved boar spermatozoa quality, inhibiting chemotaxis and phagocytosis of polymorphonuclear neutrophils toward spermatozoa.